ANALISIS KEPUTUSAN NASABAH MENABUNG: PENDEKATAN KOMPONEN DAN MODEL LOGISTIK STUDI PADA BANK SYARIAH DI MALANG - Ghozali Maski (Journal of Indonesian Applied Economics, 2010)
The aim of this research is to analyze the Islamic banking customer preferences in Malang City. Using logistic estimation, this research found that customer decision to  choose  Islamic  banking  are  influenced  by  variable  of  Islamic  banking characteristic,  services  and  trust  variable,  knowledge    variable, and  physical  of bank variable. In addition, according to logistic regression coefficient, services and trust variable have  the  largest beta coefficient which  indicated  that  variable had dominance  variable  in  influencing  customer  preferences  to  save  their money  in Islamic banking.Keywords: Customer preferences, islamic banking, component and logistic model